SERS Sensors with Bio-Derived Substrates Under the Way to Agricultural Monitoring of Pesticide Residues - Kseniya V. Serebrennikova; Nadezhda S. Komova; Anatoly V. Zherdev; Boris B. Dzantiev (Biosensors)
Uncontrolled use of pesticides in agriculture leads to negative consequences for the environment, as well as for human and animal health. Therefore, timely detection of pesticides will allow application of measures to eliminate the excess of maximum residue limits and reduce possible negative consequences in advance. Common methods of pesticide analysis suffer from high costs, and are time consuming, and labor intensive. Currently, more attention is being paid to the development of surface-enhanced Raman scattering (SERS) sensors as a non-destructive and highly sensitive tool for detecting various chemicals in agricultural applications. This review focuses on the current developments of biocompatible SERS substrates based on natural materials with unique micro/nanostructures, flexible SERS substrates based on biopolymers, as well as functionalized SERS substrates, which are close to the current needs and requirements of agricultural product quality control and environmental safety assessment. The impact of herbicides on the process of photosynthesis is considered and the prospects for the application of Raman spectroscopy and SERS for the detection of herbicides are discussed.